(untitled) (Baghdad Science Journal, 2019)
In the present study, the effects of brake pad particles of lung and liver histological sections were evaluated for (60) adult male mice. The animals were divided into three groups ( A,B,C) according to the periods of exposure (4, 8, and 12) weeks respectively exposed to brake pad particles in addition to the control groups (F) exposed to fresh air only. A special inhalation chamber designed locally has been used to expose the animals. The exposure to brake pad particles was (2.228) µg/m³ for 30 min/day, 5 days/week for (4,8and12) weeks respectively. The examination in group (A) of the histological sections of the lung showed the thickness of interalveolar septa. Also, a congestion of alveolar capillary was marked indicating pulmonary emphysema. The infiltration of alveolar macrophages showed the engulfed foreign particles (pad particles) within their cytoplasm, and peribronchial fibrosis. Group (B) showed the presence of pad particles (anthracosis), whereas the bronchial tree showed bronchitis with the bronchus-hyperplasia of mucin-producing cells (epithelial hyperplasia). Still another section showed an infiltration of mononuclear leukocytes and focal lobar necrosis. The third group (C), in turn, revealed acute interstitial bronchopneumonia with peribronchial focal necrosis and mild pulmonary edema with alveolar anthracosis. As regards the liver, group (A) showed mild central venous congestion. Group (B), on the other hand, gave acute hepatitis, congestion of the central vein hyaline degeneration and mitotic figure having 2-3 nuclei. Severe congestion of the central vein with vascular amyloid deposition and most of the hepatocytes revealed coagulate necrosis in group (C). These changing tissues increased with increasing the exposure periods and were clearer in group (C) which was exposed for 12 weeks. The continuous exposure to brake pad particles lead to damaging important body organs tissues and effect on human health, these particles can be considered as a type of pollutants added to air pollutants in different cities of Iraq.